Sports Coaching Education Students' Perspectives on Systems Thinking Models through Mentimeter Media - Fikri, Aizatul; Putri, Eka Cahyani Aulia; Dewi, Bekti Nirmala; Yulita, Fiyona; Ningrum, Ningrum; Ariyanto, Khansa Salsabila Putri (Inovasi Lokal, 2024)
Leadership is an effort made by someone with all their abilities to influence, encourage, direct, guide and mobilize other people to work with enthusiasm and confidence in achieving common goals. A person's leadership style is something important in human relations and depends on the level of maturity of the members and the goals they want to achieve. This educational activity is carried out online via Google Meet and uses an interactive lecture method to deliver the material. To warm up the media to give their opinions about leadership using the media meter given at the beginning and end of the activity. The results obtained from the initial media were regarding their response when they heard the word leader and in their opinion a leader must be able to be an example, protect and set an example for the people they lead. And in the final media minutes, to the question of what leadership model the participants chose, most of the participants chose a leadership model with a transformational thinking system when becoming a leader, because this leadership model is able to follow technological developments and advances, work professionalism demands, and changes in character. its users. Keywords: Leadership, Mentimeter, Education